2012
DOI: 10.2500/ajra.2012.26.3820
|View full text |Cite
|
Sign up to set email alerts
|

Does Oral Prednisolone Increase the Efficacy of Subsequent Nasal Steroids in Treating Nasal Polyposis?

Abstract: In the 12-week treatment evaluation of nasal polyposis, pretreatment with oral steroids had no significant advantage for most nasal symptoms other than earlier relief; however, combined oral and nasal steroid therapy more effectively improved hyposmia, polyps size, and nasal airflow. Polyps size grade 3 and/or endoscopic signs of meatal discharge predisposed to a poorer treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Combination of an oral and topical steroid affects the hyposmia, the size of the polyps and the flow of air through the nose more effectively than using them separately. Moreover, that treatment modulates nasal polyp mucosa by epithelial repair, regulation of tissue remodeling markers, increased collagen content and reduced tissue eosinophilia [ 9 , 11 , 12 ]. Preoperative oral steroids use in FESS reduced blood loss, shortened operative time and improved surgical field quality [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combination of an oral and topical steroid affects the hyposmia, the size of the polyps and the flow of air through the nose more effectively than using them separately. Moreover, that treatment modulates nasal polyp mucosa by epithelial repair, regulation of tissue remodeling markers, increased collagen content and reduced tissue eosinophilia [ 9 , 11 , 12 ]. Preoperative oral steroids use in FESS reduced blood loss, shortened operative time and improved surgical field quality [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…When data were available, meta-analysis was performed and uniformly revealed substantial efficacy of OCS in reducing nasal symptoms and nasal polyp scores 2 to 3 weeks after start of therapy. [65][66][67][68][69] When the same parameters were evaluated 10 to 12 weeks after start of therapy, the reduction in polyp score was still substantial in the OCS group but the reduction in symptom scores was not. [66][67][68] Many of these studies also revealed substantial improvements in nasal flow measurements and the sense of smell after OCS.…”
Section: Chronic Rhinosinusitis With Nasal Polypsmentioning
confidence: 99%
“…[65][66][67][68][69] When the same parameters were evaluated 10 to 12 weeks after start of therapy, the reduction in polyp score was still substantial in the OCS group but the reduction in symptom scores was not. [66][67][68] Many of these studies also revealed substantial improvements in nasal flow measurements and the sense of smell after OCS. [65][66][67][68][69] Serious adverse effects, such as peptic ulcers or osteonecrosis of the femoral head, were not reported, but there was an increase in insomnia, gastrointestinal (GI) disturbances, and dyspepsia noted in participants treated with prednisone compared with controls.…”
Section: Chronic Rhinosinusitis With Nasal Polypsmentioning
confidence: 99%
“…51 Despite the efficacy of topical steroids, when treating severely symptomatic patients, it is often preferable to prescribe short courses (Յ2 weeks) of oral steroids to acutely reduce polyp size. [52][53][54][55] Maintenance therapy with INCSs is necessary for long-term control of the inflammation that underlies CRSwNPs.…”
Section: Medical Treatment Of Crswnpmentioning
confidence: 99%